Light intensity as a growth limiting factor for the relict broadleaved spindle Euonymus latifolius (L.) Mill. in Mediterranean refugia. The need to preserve the forest canopy structure. Light intensity as a growth limiting factor for the relict broadleaved - Santiago, Alejandro; López-Serrano, Francisco Ramón; Herranz, José María; García-Saúco, Guillermo; Copete, Elena; Ferrandis, Pablo (Mediterranean Botany, 2024)
Euonymus latifolius is a paradigmatic nemoral-subMediterranean species of the relict flora from Würmian glaciations in the Iberian Peninsula. Due to its transitional nature, taxa of this plant group could be used as a sensitive indicator to evaluate the effects of climate change on plants in the near future. In the Iberian Peninsula, E. latifolius is scattered in relict, isolated small populations, and catalogued as critically endangered. Previous studies of this taxon indicated the strong dependence of recruitment on canopy cover, which was attributed to the shade-meditated maintenance of soil humidity in the juvenile microhabitat. However, no information is available on the effects of light radiation on this nemoral species. In this study, we investigated the growth response of E. latifolius to photosynthetically active radiation by producing and transplanting saplings along a broad light intensity gradient, i.e., from direct illumination to dense shaded canopy, in a nemoral mixed deciduous forest stand in the Botanic Garden of Castilla-La Mancha. Our results confirmed the marked sciophilous nature of E. latifolius, which is particularly uncommon in the Mediterranean flora, by demonstrating a drastic reduction in growth with the increase of exposure to light intensity, which became critical at high values and even lethal when plants were directly exposed to light. The opening of the canopy in the natural habitat of this species due to simplification of the structure of nemoral communities promoted by climate change in southern latitudes of Europe comprises a real and short-term risk for E. latifolius, and probably for other relict nemoral-subMediterranean species. Conservation actions are recommended.